Games for Enhancing Sustainability of Year 7 Maths Classes in Indonesia: Theory-Driven Development, Testing and Analyses of Lessons, and of Students' Outcomes - Kaune, Christa; Nowinska, Edyta; Paetau, Annika; Griep, Mathilda (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2013)
The results of international comparative studies have shown that relationships exist between metacognition and cognitive activation and learning success. Since 2007 we have been carrying out projects in Indonesia to improve cognitive and metacognitive activities of pupils of year 7 and their teachers. These activities are to contribute to the construction and sensible use of sustainable mental models for mathematical concepts and methods by learners. This paper shows how games are used for the enhancement of metacognitive and discursive activities in class. Their effectiveness is documented exemplary by means of students' outcomes and transcripts of lessons from project classes.Keywords: Cognitive Activation, Metacognition, Games, IntegersÃ‚Â DOI: http://dx.doi.org/10.22342/jme.4.2.412.129-150